41 seconds to freedom an insider's account of the Lima Hostage Crisis, 1996-97 - Giampietri, Luis; Salisbury, Bill; Ausejo, Lorena, 1962- (Ballantine Books, 2007)
In 1996, members of the Tupac Amaru Revolutionary Movement raided a party at the official residence of Japan's ambassador to Peru. With a huge array of weapons, the militants took hostage hundreds of high-level diplomats, government and military officials and business executives. This book tells the extraordinary story of the hostage rescue.